KONSEP KEPALA KELUARGA ANTARA LAKI-LAKI DAN PEREMPUAN DALAM SURAT AN NISA (4) AYAT 34 - Muhammad Nur Kholis (Istinbath : Jurnal Hukum, 2015)
Husband's role in the family is affected by the role of the wife. Harmonious domestic life is the desire of every couple who fostered by the head of the family both men and women. But in practice conditions many families are affected by the threat of hurricanes and the current inequality of a leadership role. The relationship between husband and wife at a given time can suffer shocks worrying. Tali marriage in Islam is a strong bond that is formed couples in order to reach the fabric of household. In al-Qur'an Allah characterization of his marriage with the term mitsaqan ghalizhan (rope solid agreement). This article attempts to explain the relationship between the holy book the Koran and the community, both of which are factors that have a dependency memenculkan different interpretations, particularly of the concept of "head of household". In other words, changes in the condition and development is a means to understand the scope of the meaning of al-Qur'an.